THE BARRIERS OF SMEs MALAY EMPLOYERS ON HALAL CERTIFICATION APPLICATION AT KEDAH DARUL AMAN - Nur Sabrina Hashim; Ahmad Rosli Mohd Nor; Norazlan Anual (Journal of Islamic, Social, Economics and Development, 2023)
Based on corporate status and industry, statistics from 2010 to 2022 on requests for halal certification in Kedah reveal a low amount of requests. In comparison to the real number of Malay small and medium industry enterprises in Kedah, only 219 Malay employers have applied. 408 of the 629 applications come from non-Bumiputras, and the remaining 529 are from Malay company owners. A comparatively modest number of firms with Malay ownership have applied for halal certification. This essay seeks to comprehend the steps and processes involved in applying for halal certification, the significance of a halal certificate for the sector, and the obstacles Malay employers in the SMEs industry have when seeking for a halal certificate. Thus, it is crucial to recognise the significance of halal certification for this industry and examine the obstacles that Malay employers face when applying for halal certificates in the Bumiputera sector. With the use of the qualitative research approach, this study highlights the depth of the data. Interviews were conducted with ten Kedah-based industrial company managers. The respondents in this study were chosen through the use of purposeful sampling. In-depth interviews gave researchers the chance to gather detailed information about the thoughts and actions of these businessmen, particularly with regard to halal certification. Five obstacles are getting in the way of them obtaining Malaysian Halal Certification, according to the interviewees. The difficulties were listed as being time limits, lack of guidance and directions, cost, ignorance of the halal standard, stringent procedures, and severe procedures. Because such initiatives are in line with JAKIM's objective to ensure enforcement and compliance with standards halal in this country, JAKIM should implement effective information and awareness campaigns, especially for Malay entrepreneurs.